Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

C'est le soleil qui m'a brûlée - Beyala, Calixthe (Editions J'ai Lu, 1988)
"La tête dans les odeurs de l'homme, la bouche contre son sexe, elle se dit qu'il est devenu complètement fou, qu'elle est devenue complètement folle (...). Dans l'état actuel de l'histoire, quoi qu'elle fasse, quoi qu'elle dise, elle aura toujours tort. L'homme c'est lui." Cameroun. Chaleur humide, ciel hypnotique. Dans le bidonville où elle a grandi, abandonnée par sa mère, Ateba cherche avec désespoir sa place dans une société où la femme n'a qu'un droit : se taire. Ecartelée entre plusieurs sentiments contraires, la jeune fille, le ventre en feu, la haine au coeur, est certaine qu'elle peut devenir un jour la plus forte. Incapable de se résoudre à concilier sexe et asservissement, elle refuse de passer sa vie à genoux.–Quatrième de couverture.
Section: 152 pages
Keywords: afrique; afro-féminisme; approches et analyses; arts; cameroun; cours; discipline; féminisme africain; lit2815; premier cycle; roman; régions géographiques; sexisme; systèmes d'oppressions; études littéraires